The determination of microbial species diversity and evenness in activated sludge systems using different biolog systems - Cloete, T.E. (Thomas Eugene), 1958- (University of Pretoria, 2013)
Dissertation (MSc Agric (Microbiology))--University of Pretoria, 2006.